The Effect of Learning Technique and Reading Interest Towards Students' Listening Skill - Mida Sulfiana (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: This research aims to determine the effect of learning technique and reading interest toward students' English listening skill. This research is an experimental type. The instruments used were written tests and questionnaires. The results of this research showed there is an effect between learning techniques and reading interests toward students' Listening skills. There are significant differences between students having high and low reading interest. Those who learned with Dictogloss Technique have higher reading interests than those who learned with Traditional Dictation Technique. Meanwhile, students having low reading interests who learned with Dictogloss Technique and Traditional Dictation have no significant difference in English listening skills. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh teknik pembelajaran dan minat baca terhadap keterampilan menyimak bahasa Inggris mahasiswa. Penelitian ini merupakan jenis penelitian eksperimen. Instrumen yang digunakan adalah instrumen tes dan kuesioner. Hasil penelitian ini menunjukkan bahwa terdapat interaksi antara teknik pembelajaran dan minat baca terhadap keterampilan menyimak bahasa Inggris, terdapat perbedaan keterampilan menyimak antara kelompok mahasiswa dengan minat baca tinggi dan rendah yang belajar dengan teknik dictogloss darpada yang belajar dengan teknik traditional dictation, hasil keterampilan menyimak kelompok mahasiswa dengan minat baca rendah yang belajar dengan teknik dictogloss dan teknik traditional dictation tidak menunjukkan adanya perbedaan yang signifikan.